The Impact of Plasma Intensity on the Unused Rate in Semiconductor Manufacturing: Comparative Analysis Across Intensity Ranges from 30 to 3000 - Dae Kee Min; Jiyun Woo; Jinwook Kim; Bong-Jae Lee; Eui-chan Jeon; Joohee Lee (Applied Sciences, 2025)
This study examines the impact of plasma intensity on the process unused rate, expressed as 1-Ui, within semiconductor manufacturing. Since the influence of plasma level on 1-Ui is inconsistent without considering gas, the experimental data were analyzed after grouping plasma levels by intensity. Plasma intensity is classified into three categories: low (<100), medium (500–700), and high (>1000). The dataset includes seven columns and 8324 entries representing seven gases—NF3, SF6, CH2F2, CHF3, C4F6, C4F8, and CF4. To analyze the relationship between plasma intensity and 1-Ui, we conducted a series of ANOVA tests followed by post hoc analyses to identify statistically significant differences in 1-Ui across the defined plasma intensity levels.